The Influence of Motorcyclists’ Attitudes on Traffic Accidents and Offences - D. M. Priyantha Wedagama (Jurnal Teknik Sipil, 2017)
Abstract This study aims at identifying determinants of motorcyclists’s attitudes and analysing their influences on the occurrence of traffic accidents and offences. A self-reported questionnaire survey was distributed in year 2016 among a representative sample of motorcyclists in Denpasar, Bali. The questionnaire consisted variables of socioeconomic factors, the use of motorcycle and riding history, learning method and experience on riding motorcycles, motorcyclist attitudes and involvement in traffic accidents and offences. The results show that age and education level influenced learning method and experiences variables while gender did on motorcyclists’ attitude. In addition, learning method and experience and motorcyclists’ attitudes on the road were two significant factors respectively that negatively affected motorcyclists’ involvement in traffic accidents and offences. In other words, ages, education level and gender have significant indirect influences on motorcyclists’ involvement in traffic accidents and offences. The influence of gender implies that compared to females, male motorcyclists are more likely to fail giving priority and violate parking signs. In comparison with females, male motorcyclists therefore, are more likely to get involved in traffic accidents and offences. Interestingly, this study indicated that motorcyclists with a higher education were not a guarantee not to involve in traffic accidents and offences. Abstrak Penelitian ini bertujuan untuk identifikasi faktor-faktor penentu sikap pengendara sepeda motor dan pengaruhnya terhadap terjadinya pelanggaran dan kecelakaan lalu lintas. Pengambilan data dilakukan pada tahun 2016 dengan menyebarkan kuesioner kepada pengendara sepeda motor di Denpasar, Bali. Kuesioner memuat variabel-variabel sosial ekonomi, rekam penggunaan sepeda motor, teknik latihan dan pengalaman berkendara dengan sepeda motor, sikap pengendara motor dan keterlibatan terkait pelanggaran dan kecelakaan lalu lintas. Hasil penelitian menunjukkan bahwa usia dan tingkat pendidikan berpengaruh kepada teknik latihan dan pengalaman berkendara sementara jenis kelamin berpengaruh pada sikap pengendara sepeda motor. Teknik latihan dan berkendara dan sikap pengendara sepeda motor adalah dua faktor penting yang berdampak negatif terhadap keterlibatan pengendara sepeda motor dalam pelanggaran dan kecelakaan lalu lintas. Usia, tingkat pendidikan dan jenis kelamin memiliki pengaruh tidak langsung pada keterlibatan pengendara sepeda motor dalam pelanggaran dan kecelakaan lalu lintas. Pengendara sepeda motor pria, dibandingkan dengan wanita, mempunyai kemungkinan untuk tidak memberikan prioritas kepada pengendara bermotor lainnya dan pelanggaran rambu lalu lintas (parkir). Dengan perkataan lain, pengendara sepeda motor laki-laki di Denpasar, mempunyai kemungkinan terlibat pelanggaran dan kecelakaan lalu lintas. Penelitian ini juga memperlihatkan bahwa pengendara sepeda motor dengan pendidikan tinggi bukan jaminan tidak terlibat dalam pelanggaran dan kecelakaan lalu lintas.